Evaluation of the Accuracy of Human Kallikrein6, Cancer Antigen125, and Human Epididymis 4 in Predicting Ovarian Cancer - Wenas, Yongki; Suwiyoga, Ketut; Sanjaya, I Nyoman H (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To evaluate the accuracy of hK6, HE4, and CA125 in predicting the malignancy of ovarian mass. Methods: The design of this study was cross-sectional. This study was conducted in the Obstetrics and Gynecology Clinic, Sanglah Hospital, Denpasar, between the period of September 2014 and August 2016. Samples were all patients with ovarian tumors who underwent surgery at Sanglah Hospital, Denpasar. Data analysis was performed using McNemar and chi square test in SPSS for windows version 17.0. Results: 22 samples were obtained. P > 0.05 value of age and parity variables indicated no differences between the two groups. There is no accuracy differences (sensitivity, specificity, positive predictive value, negative predictive value) of hK6 compared to histopathology examination in diagnosing ovarian cancer (p = 1). There is no accuracy differences (sensitivity, specificity, positive predictive value, negative predictive value) of HE4 compared to histopathology examination in diagnosing ovarian cancer (p = 1). There is no accuracy difference (sensitivity, specificity, positive predictive value, negative predictive value) of CA125 compared to histopathology examination in diagnosing ovarian cancer (p = 0.687). Conclusion: There was no accuracy differences (sensitivity, specificity, positive predictive value, negative predictive value) found between hK6, CA125, HE4 compared to histopathology examination in predicting ovarian cancer. [Indones J Obstet Gynecol 2017; 5-2: 110-113] Keywords: cancer antigen 125, human epididymis-4, human kallikrein 6, ovarian cancer